PEMBERDAYAAN MASYARAKAT DESA CUCUM KECAMATAN KUTA BARO KABUPATEN ACEH BESAR MELALUI OPTIMALISASI PENGELOLAAN LAHAN PEKARANGAN - Mujiburrahmad Mujiburrahmad; Akhmad Baihaqi; Ira Manyamsari (Gapenas Publisher, 2022)
The knowledge and skills of women farmers in Cucum Village, Kuta Baro District, Aceh Besar Regency in terms of vegetable cultivation, as well as the use of agricultural facilities and infrastructure (saprodi) in general are still limited. The purpose of the economic empowerment activity for the poor is to increase the knowledge and skills of partner groups regarding vegetable cultivation, business management and the provision of production facilities and infrastructure to increase production and income. The main obstacle in increasing income is the limited working capital in carrying out vegetable cultivation in the yard. Overcoming these problems, three lecturers from Syiah University facilitated the Community Empowerment of Cucum Village, Kuta Baro District, Aceh Besar District through Optimizing the Management of Yard Land. This activity will be carried out in Cucum Village, Kuta Baro District, Aceh Besar Regency from July to October 2021. The implementation of this activity includes training and procurement of production inputs. The targets and outcomes of this activity are to increase knowledge and skills in correct vegetable cultivation using environmentally friendly planting media, as well as business management training for women farmers to provide understanding and knowledge in running a business, measured and well planned. Another benefit is that the target audience gets facilities and infrastructure for vegetable cultivation. Besides the output of this research, it will produce publications through electronic media and scientific journal publications. Based on the results of the Community Empowerment of Cucum Village, Kuta Baro District, Aceh Besar Regency through Optimization of Yard Land Management, it can be concluded that partners have increased knowledge and skills in using environmentally friendly planting media that have economic value that can be used for vegetable cultivation. The availability of facilities and infrastructure (saprodi) for vegetable farmers is expected to increase production yields while at the same time increasing their economy and welfare. In addition, the result of this activity is that women farmers really have a direction in running a business, measured, and well planned.